Paralympic Sports Medicine — Current Evidence in Winter Sport: Considerations in the Development of Equipment Standards for Paralympic Athletes - Burkett, B. (Clinical Journal of Sport Medicine, 2012)
Objective: To highlight and discuss the considerations for the future development of equipment standards for Winter Paralympic sports.